Loeys–Dietz syndrome caused by 1q41 deletion including TGFB2 is associated with a neurodevelopmental phenotype. Issue 7 (15th April 2022) - Fry, Deanna; Groepper, Daniel; MacCarrick, Gretchen; Demo, Erin M.; Thomas, Matthew J.; Wilkes, Margaret J.; Lyons, Michael J.; Tucker, Megan E.; Steding, Catherine; Fleischer, Julie
Abstract: Loeys–Dietz syndrome (LDS) is a connective tissue disorder that commonly results in a dilated aorta, aneurysms, joint laxity, craniosynostosis, and soft skin that bruises easily. Neurodevelopmental abnormalities are uncommon in LDS. Two previous reports present a total of four patients with LDS due to pure 1q41 deletions involving TGFB2 (Gaspar et al., American Journal of Medical Genetics Part A, 2017, 173, 2289–2292; Lindsay et al., Nature Genetics, 2012, 44, 922–927). The current report describes an additional five patients with similar deletions. Seven of the nine patients present with some degree of hypotonia and gross motor delay, and three of the nine present with speech delay and/or intellectual disability (ID). The smallest deletion common to all patients is a 785 kb locus that contains two genes: RRP15 and TGFB2 . Previous studies report that TGFB2 knockout mice exhibit severe perinatal anomalies (Sanford et al., Development, 1997, 124, 2659–2670) and TGFB2 is expressed in the embryonic mouse hindbrain floor (Chleilat et al., Frontiers in Cellular Neuroscience, 2019, 13). The deletion of TGFB2 may be associated with a neurodevelopmental phenotype with incomplete penetrance and variable expression.